Politik Kewargaan Dimensi Hak bagi Penghayat Kepercayaan di Indonesia - Cantika, Yayang Firdianda; Maryanah, Tabah (Jurusan Ilmu Politik Universitas Bangka Belitung, 2026)
Adherents of indigenous beliefs represent belief systems rooted in local traditions that continue to be preserved by local communities. As of 2024, the number of adherents of indigenous beliefs reached 98,822 individuals, or approximately 0.003% of the total population. In Indonesia, adherents of indigenous beliefs continue to face limitations in legal recognition and the fulfillment of their rights. This study aims to provide a deeper understanding of the legal recognition and rights of adherents of indigenous beliefs, the forms of discrimination in the implementation of the Constitutional Court decision, and to identify the factors that hinder the effective implementation of the Constitutional Court ruling. This research employs a descriptive qualitative method based on document analysis. Data were collected through the examination of government documents related to the recognition of the legal status of adherents of indigenous beliefs. The collected data were subsequently analyzed using a qualitative approach with content analysis techniques. The findings indicate that Constitutional Court Decision No. 97/PUU-XIV/2016 represents the provision of a civil rights dimension; however, in practice, the implementation of these rights remains constrained, thereby hindering the fulfillment of social rights for adherents of indigenous beliefs. Discrimination persists in population administration, access to education, and burial arrangements. Such discrimination is influenced by factors including the limited competence of administrative officers, the lack of integration of educational services for adherents of indigenous beliefs, minimal public dissemination of the Constitutional Court decision, and weak law enforcement against violence and discriminatory practices targeting adherents of indigenous beliefs.